Friction dependence on surface patterns - Lim, Xinglin. (2013)
As study of friction is an important aspect in most engineering and industrial applications, this report would cover a further study in said area. Experimentation was carried out on various substrates with varying surfaces: smooth, isotropic and anisotropic. Each substrate surface will present a different surface roughness, hence a comparison will be done between the three surfaces to analyse the effect of the surface roughness of the surfaces in relation to the static friction.